A new allele, HLA‐C*08:228, identified by sequence‐based typing in a Korean individual. (16th September 2021) - Kim, Chris Gunwoo; Kwon, Oh‐Joong; Park, Yong; Cho, Yunjung
Abstract : The new allele C*08:228 showed one nucleotide difference from C*08:01:01 in codon 36 (TTC −> TTG).